Evaluation of casein supplementation on periodontal and mandibular bone of rats fed standard diet and cafeteria diet (Research, Society and Development, 2021)
Objective: To evaluate the effect of casein supplementation on the periodontium and mandibular bone of rats fed a standard diet and a cafeteria diet. Methodology: 24 Wistar rats were divided into four experimental groups: normal diet (DN), normal diet with casein (DNC), cafeteria diet (DC) and cafeteria diet with casein (DCC). The DNC and DCC groups received 2 mL of micellar casein from the 60th to the 90th day. At 90 days, the animals were orthouthanized and the materials were collected for analysis. Results: The animals in the DC and DCC groups showed a higher adiposity index compared to DN and DNC (p